Transformations in the global political economy - Pirages, Dennis C (ed.); Sylvester, Christine (ed.) (London, 1990)
Over the last two decades the global political economy has been dramatically transformed in many ways that we are just now beginning to understand. And the pace of these transformatins is accelerating as we move toward the next century. This book brings together a collection of essays that focus on the various dimensions of this transformation and prospects for future changes. The book begins with an analytical essay that offers an overview of causes of change in the global political economy. This is followed by chapters that analyze transformations in oil, food and other raw materials markets. The rest of the book focuses on changing issues of trade and developments as they affect the prospects of the industrial countries, the newly industrializing coutries and the less developed world.
Keywords: Economics